2014
DOI: 10.1155/2014/925762
|View full text |Cite
|
Sign up to set email alerts
|

Gradually Increased Training Intensity Benefits Rehabilitation Outcome after Stroke by BDNF Upregulation and Stress Suppression

Abstract: Physical training is necessary for effective rehabilitation in the early poststroke period. Animal studies commonly use fixed training intensity throughout rehabilitation and without adapting it to the animals' recovered motor ability. This study investigated the correlation between training intensity and rehabilitation efficacy by using a focal ischemic stroke rat model. Eighty male Sprague-Dawley rats were induced with middle cerebral artery occlusion/reperfusion surgery. Sixty rats with successful stroke we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 41 publications
3
34
0
3
Order By: Relevance
“…BDNF has been reported to have a neuroprotective effect against brain injury and is thought to be potent candidates in the recovery from cerebral ischemia [32,33]. BDNF could support the neuron survival and encourage neuron and synapse growth and differentiation, and is related to neuroplasticity and contributes to neural rehabilitation after stroke [34]. Taken together, BDNF can increase synaptic plasticity and neurogenesis by upregulating the expressions of synaptophysin and has a promotional role in neural functional recovery which is confirmed by lower balance beam walking score, rotating bar walking score, and screen test score.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF has been reported to have a neuroprotective effect against brain injury and is thought to be potent candidates in the recovery from cerebral ischemia [32,33]. BDNF could support the neuron survival and encourage neuron and synapse growth and differentiation, and is related to neuroplasticity and contributes to neural rehabilitation after stroke [34]. Taken together, BDNF can increase synaptic plasticity and neurogenesis by upregulating the expressions of synaptophysin and has a promotional role in neural functional recovery which is confirmed by lower balance beam walking score, rotating bar walking score, and screen test score.…”
Section: Discussionmentioning
confidence: 99%
“…This was observed in all the patients who had been administered a neuromotor regime for 2 months. Patients in group 2 showed a statistically significant increase (baseline to 8 weeks) in BDNF as compared to VEGF (p = 0.01 vs. p = 0.53) indicating that BDNF is more likely to be involved in neuroplastic changes, which is supported by the literature [36]. Several animal studies have demonstrated significantly increased BDNF mRNA levels in the rat hippocampus after a single bout of 6 h voluntary wheel running [37].…”
Section: Discussionmentioning
confidence: 71%
“…çîíû èøåìèè è óëó÷øàþò íåâðîëîãè÷åñêèå èñõîäû [14][15][16][17][18]. Ó÷åíûìè âûÿâëåíà ïîëîaeèòåëüíàÿ êîððåëÿöèîííàÿ âçàèìîñâÿçü ìåaeäó ïîâûøåíèåì óðîâíÿ íåéðîòðîôè÷åñêèõ ôàêòîðîâ è ÷àñòîòîé ôèçè÷åñêèõ óïðàaeíåíèé [19,20].…”
Section: __________________________unclassified